Effects of vegetable oil supplementation on rumen fermentation and microbial population in ruminant: A review - Nur Atikah Ibrahim; Abdul Razak Alimon; Halimatun Yaakub; Anjas Asmara Samsudin; Su, Candyrine Chui Len; Wan Nooraida Wan Mohamed; Abidah Md Noh; Muhammad Amirul Fuat; Saminathan Mookiah (Springer, 2021)
Understanding the nature of ruminant nutrition and digestion is essential to improve feeding management and animal production. Among many approaches, manipulating ruminant nutrition and fermentation through feed supplementation is being practised and researched. Over the last decade, the utilization of vegetable oils in feed formulation and their efects on various aspects of ruminants have been reported by many researchers. It is important to understand the lipid metabolism in ruminants by microorganisms because it afects the quality of ruminant-derived products such as meat and milk. Majority of vegetable oil supplementation could reduce rumen protozoa population in ruminants due to the efects of medium-chain fatty acids (FAs). However, vegetable oil also contains unsaturated FAs that are known to have a negative efect on cellulolytic bacteria which could show inhibitory efects of the fbre digestion. In this paper, the physiology of nutrient digestion of ruminants is described. This paper also provides a current review of studies done on improvement and modifcation of rumen fermentation and microbial population through vegetable oil supplementation.